Visual outcome of cataract surgery with IOL implantation in traumatic cataract among 189 children: The Lahan experience - Puri, L R; Shrestha, G S (Journal of Chitwan Medical College, 2017)
Trauma is an important cause of monocular blindness in the developing world. This study aims to determine the demographic profile and visual outcome of cataract surgery among the children with traumatic cataract. It was a prospective and longitudinal study of 189 consecutive children below 16 years who underwent cataract surgery with intra ocular lens (IOL) implantation for traumatic cataract at Sagarmatha Choudhary Eye Hospital, Lahan, Nepal from October 2012 to March 2014. Assessment included visual acuity measurement in the Snellen’s chart or the Cardiff card, anterior segment examination with slit lamp, dilated fundus examination with the help of +20D lens in indirect ophthalmoscope, B-scan ultrasonography of posterior segment and objective and subjective refraction. Follow up was scheduled at first post-operative day, at discharge, one month and three months. Cause and type of trauma, demographic factors, surgical intervention, complications, and visual acuity was recorded. Among 189, majority of them were males (73%) and the average age was 8.8±3.6 years. The time of presentation ranged from 3 days to 8 years (median age two months). Wooden stick was the most common cause of injury (34.4%). The average preoperative visual acuity in logMAR scale was 1.6. The average postoperative visual acuity in logMAR scale was 0.8. Eye injuries with traumatic cataract are associated with significant visual impairment. Cataract surgery with intraocular lens implantation restores vision significantly.